2015
DOI: 10.1002/cam4.438
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐species identification of a plasma microRNA signature for detection, therapeutic monitoring, and prognosis in osteosarcoma

Abstract: Osteosarcoma (OS) is the primary bone tumor in children and young adults. Currently, there are no reliable, noninvasive biologic markers to detect the presence or progression of disease, assess therapy response, or provide upfront prognostic insights. MicroRNAs (miRNAs) are evolutionarily conserved, stable, small noncoding RNA molecules that are key posttranscriptional regulators and are ideal candidates for circulating biomarker development due to their stability in plasma, ease of isolation, and the unique e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 23 publications
2
63
0
Order By: Relevance
“…Previous studies have demonstrated that miR-214 functions either as an oncogene or a tumor suppressor in a number of human cancer types, including lung, prostate, colorectal and esophageal cancer (15)(16)(17)(18). Previous studies have indicated that elevated miR-214-3p is associated with OS progression, but a limited number of studies have focused on the function and mechanism of miR-214-3p (10,11,19,20). In a previous study by the authors, it was demonstrated that upregulated miR-214 expression was associated with aggressive clinicopathological features (tumor size, metastasis status and response to pre-operative chemotherapy) and poor prognosis of pediatric osteosarcoma (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that miR-214 functions either as an oncogene or a tumor suppressor in a number of human cancer types, including lung, prostate, colorectal and esophageal cancer (15)(16)(17)(18). Previous studies have indicated that elevated miR-214-3p is associated with OS progression, but a limited number of studies have focused on the function and mechanism of miR-214-3p (10,11,19,20). In a previous study by the authors, it was demonstrated that upregulated miR-214 expression was associated with aggressive clinicopathological features (tumor size, metastasis status and response to pre-operative chemotherapy) and poor prognosis of pediatric osteosarcoma (11).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that miR-214 may function as a tumor suppressor and may have a tumorigenic role. In previous studies, researchers have demonstrated that miR-214 was upregulated in osteosarcoma and associated with tumor progression and poor prognosis (10,11). However, little progress has been achieved in terms of elucidating the molecular mechanisms of miR-214-3p-mediated tumorigenesis in OS.…”
Section: Introductionmentioning
confidence: 99%
“…GEO (http://www.ncbi.nlm.nih.gov/geo) is a public functional genomics data repository for high‐throughput gene expression data, different types of microarrays and chips [9]. The miRNA microarray datasets (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE69470 [10], http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE28425 [11] and http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE65071 [12]) were downloaded from GEO (GPL20275, GPL8227 and GPL19631 platform, respectively), and we performed an integrated analysis. Comprehensive miRNA expression profiling was obtained by using the probes in the platforms mentioned earlier.…”
Section: Methodsmentioning
confidence: 99%
“…42 If the experiment is using an array-based method with hundreds of microRNAs, a global normalization approach may be useful. 33,43 Many microRNAs Figure 3. microRNA-seq normalization (RPM) is a dependent normalization.…”
Section: Microrna-seq Alignmentmentioning
confidence: 99%
“…AllenRhoades et al designed a study to identify plasma microRNAs that could detect and monitor childhood osteosarcoma. 43 The first component was performed in an osteosarcoma mouse model. After power calculations were performed on how many animals would be required, human osteosarcoma tumors were grown in nude mice with serial plasma collections over time.…”
Section: Case Studies To Identify Rigor and Reproducibility Challengementioning
confidence: 99%